Jona Heita's transcript, Namibia, July 20 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
To have access to the research data file, please contact: Jona Heita jheita@unam.na
Keywords: Arid regions; Travel; Tourism; Government; Pastoralist; Conservancy; Lockdown; Sociality; Namibia; Mobility; COVID-19 Pandemic